Märterlus kui religioosne ja poliitiline mõjutusvahend (islami ja kristluse näitel) - Engman, Kristel (Usuteaduslik Ajakiri, 2011)
Aspects of Martyrdom as Religious and Political Measures Using the Examples of Islam and Christianity Martyrdom as a means of religious and political influence has been gaining in importance in both internal and foreign affairs of the states, as well as in cultural and religious relations. Introduced mainly in the religious contexts up to the 20th century, nowadays martyrdom has spread over the borders of religion becoming a part of political discourse. Noteworthy is the intertwining of religious martyrdom with political ambitions. This article relates to the concepts of martyrdom in Christianity and Islam. Paying heed to the blurring distinction between martyrdom and religious terrorism, the article analyses terrorism justified on religious grounds as a drastic means of influence in the far-reaching world of religion and politics, giving special attention to the increasingly frequent use of one of its manifestations – suicide terrorism. Martyrdom is one of the most powerful instruments of religious and political pressure, which is aimed at influencing the views of potential martyrs in terms of personal eschatology, increasing the faith and religious zeal of the followers of similar convictions, strengthening joint identity and pressurising certain developments into the direction that result in martyr deaths desired by certain interest groups. In Christianity and Islam, a martyr was originally a witness, somebody who was ready to die in the name of his/ her religious beliefs, not for the political objectives. Even though martyrdom stories as narratives have formed an inseparable part of different cultures and religions for thousands of years, clear distinction between the religious and political martyrdom is becoming more and more indistinct. In neither religious nor political spheres the need for martyrdom stories does not seem to be on the decline; but as an act of sacrifice the ways of martyrdom and the number of people involved, either willingly or unwillingly, in the act are undergoing changes.